The value of ultrasonography combined with carbohydrate antigen 125 and 19-9 detection in the diagnosis of borderline ovarian tumors and prediction of recurrence - Niu, Lina; Wang, Weibin; Xu, Yongjun; Xu, Tao; Sun, Jiali; Lv, Weiqin; Zhang, Junli; Qiu, Lirong; Dong, XuFeng; Shang, Yun; Zhang, Lizhen; Wang, Junxia (Frontiers in Surgery, 2023)
Objective: This study aimed to investigate the clinical value of ultrasonography combined with tumor markers in the diagnosis and prediction of recurrence of borderline ovarian tumors (BOTs) and analyze the value of the combination of two different auxiliary examinations in the diagnosis and prediction of recurrence of BOTs. Methods: Here, 221 patients with BOTs confirmed by postoperative pathology were enrolled. Their clinical data, including the ultrasonography features, tumor markers, and clinicopathological data, were retrospectively analyzed. Results: The statistical data of the 221 cases with BOTs were as follows: 94 (42.5%) with left-sided lesions, 102 (46.2%) with right-sided lesions, and 25 (11.3%) with bilateral lesions. Moreover, 93 cases (42.1%) had a borderline serous tumor, 110 (49.8%) had a borderline mucinous tumor, 12 (5.4%) had a borderline serous mucinous tumor, 2 (0.9%) had a borderline endometrioid tumor, 1 (0.5%) had a borderline Brenner tumor, and 2 (0.9%) had a clear cell BOT. There were 104 cases (47.1%) with a tumor diameter of ≤10 cm and 117 cases (52.9%) with a tumor diameter of >10 cm as suggested by ultrasonography. There were 89 cases (40.3%) with septation, 44 (19.9%) with papilla, and 97 (43.9%) with blood flow as demonstrated by ultrasonography. Carbohydrate antigen 125 (CA 125) was elevated in 132 cases (59.7%), and CA 19-9 was elevated in 52 cases (23.5%). Conclusion: In general, BOTs are difficult to diagnose preoperatively and have a certain recurrence rate. Ultrasonography combined with CA 125 and CA 19-9 is significant for the preoperative diagnosis and selection of surgical modality for BOTs and could be used as a guideline to achieve good preoperative preparation and avoid secondary surgery.